Caracterización clínica de pacientes con pseudoexfoliación en estudio multicéntrico y asociación a ancestría mapuche-huilliche - Romero C., Pablo Tomás; Mena A., Eguzki; Olguín O., Danilo; Herrera C., Luisa (Revista Hospital Clínico Universidad de Chile, 2023)
Introduction: Pseudoexfoliation Syndrome (PEX) is a multisystemic disease. It is the most common cause of secondary glaucoma, which has a faster progression and worse prognosis. Objective: Description of epidemiological and ophthalmological clinical characteristics in patients with PEX at Universidad de Chile Clinical Hospital, San José Hospital, and Félix Bulnes Hospital. Methods: Multicenter descriptive study. Clinical records of patients with pseudoexfoliation glaucoma from the past 5 years were reviewed in 3 centers located in the Metropolitan Region. Epidemiological, clinical, treatment, and documented complication characteristics were analyzed. Furthermore, to analize a possible association between pseudoexfoliation glaucoma and Mapuche-Huilliche ethnicity we used a control group that included patients with primary open-angle glaucoma and no PEX. Results: Of 190 eyes from 95 patients, 172 with PEX-related glaucoma (GPEX) were included in the study, 56 were males and 39 females, with an average age of 76,7 years (range 58-92 years). 34,% had a family history of glaucoma. 15,8% (15 patients) had at least one surname of Mapuche origin and 11,6% had two last names. An association was found between the Mapuche-Huilliche ethnicity and the diagnosis of GPEX compared to the control group (Fisher’s exact test p = 0.007). In the 172 analyzed eyes, the average intraocular pressure was 17,9 (range 7-52). 92 eyes had a visual acuity (VA) <0.05, of which 29,9% had no light perception, and 80 eyes had VA ≥0.05. The average cup-to-disc ratio was 0.76. Mixed cataract was the predominant type, accounting for 56,8% of the total of cataracts, and 19,8% had hypermature/mature cataract. 24 eyes in the total sample had ocular complications, with central retinal vein thrombosis being the most common (5,2%), followed by phacodonesis or lens subluxation (3,5%). The modal number of medications used was 2, and in terms of surgical management 10,5% underwent trabeculectomy, 1,7% received drainage implant, and 23,3% had selective laser trabeculoplasty. Conclusion: PEX-related glaucoma in the studied population is a disease that occurs at an older age, leading to severe visual impairment due to the severity of glaucoma. Our findings indicate an association of GPEX and Mapuche-Huilliche ethnicity. Lastly, the importance of early diagnosis and treatment of this condition is emphasized given its high rate of blindness and complications in the studied sample.